Geographic versus industry diversification: constraints matter - Paul Ehling; Sofia Brito Ramos (European Central Bank (ECB), 2005)
This research addresses whether geographic diversification provides benefits over industry diversification. In the absence of constraints, no empirical evidence is found to support the argument that country diversification is superior. With short-selling constraints, however, the geographic tangency portfolio is not attainable by industry portfolios. Results with upper and lower constraints on portfolio weights as well as an out-of-sample analysis show that geographic diversification almost consistently outperforms industry portfolios, although we cannot establish statistical significance.
Keywords: G11; G15; 330; block-bootstrap tests; Diversification gains; EMU; geographic diversification; industry diversification; Portfolio-Management; Risikoaversion; Kapitalanlage; Theorie